Mechanical and electrical properties of Si-SiC fabricated using SiC-C composite powders synthesized by sol-gel process - Youn, S.I.; Cho, G.S.; Youm, M.R.; Lim, D.S.; Park, S.W. (Korean Ceramic Society, 2014)
In this study, Si-SiC composites were fabricated using a Si melt infiltration method using β-SiC/C composite powders synthesized by the carbothermal reduction of SiO2-C precursors made from a TEOS and a phenol resin. The purity of the synthesized SiC-C composite powders was higher than 99.9993 wt% and the average particle size varied from 4 to 6 μm with increasing carbon contents of the SiO2-C precursors. It was found that the Si-SiC composites fabricated in this study consist of β-SiC and residual Si, without any trace of α-SiC. The 3-point bending strengths of the fabricated Si-SiC composites were measured and found to be higher than 550 MPa, although the density of the fabricated Si-SiC composite was less than 2.9 g/cm3. The bending strengths and the densities of the fabricated Si-SiC composites were found to decrease with increasing C/Si mole ratios in the SiC-C composite powders. The specific resistivities of the Si-SiC composites fabricated using the SiC-C composite powders were less than 0.018 Ωcm. With increasing C content in the SiC-C composite powders used for the fabrication of Si-SiC composites, the specific resistivity of the Si- SiC composites was found to slightly increase from 0.0157 to 0.018 Ωcm. ？ 2014, The Korean Ceramic Society. All rights reserved.
Keywords: Silicon carbide; Composite powders; Mechanical and electrical properties; RBSC; Specific resistivities; Bending strength